364 Use of Blinded Hypnotic Tapering for Hypnotic Discontinuation: Final Report. (3rd May 2021) - Edinger, Jack; Wamboldt, Frederick; Holm, Kristen; Johnson, Rachel; Simmons, Bryan; Tsai, Sheila; Morin, Charles
Abstract: Introduction: Many patients have difficulties achieving hypnotic discontinuation due to anxiety that arises when they knowingly reduce their hypnotic dose or withhold it entirely. This study tested a blinded tapering approach to reduce patients' anxiety and help them discontinue their hypnotics. Methods: The study sample included 78 (M age = 55.2 ± 12.8 yrs.; 65.4% women) users of benzodiazepine and benzodiazepine receptor agonists. Following baseline assessments, enrollees first completed 4 sessions of cognitive behavioral insomnia therapy (CBTI). Subsequently they were randomized to one of three 20-week, double-blinded tapering protocols wherein their medication dosage either remained unchanged (CTRL) or was reduced by 25% or 10% every two weeks. At the end of the 20-week period the study blind was eliminated and those who completed one of the two blinded tapering protocols entered a 3-month follow-up period, whereas CTRL participants were offered an open label taper before completing the follow-up. Results: Among those who completed one of the blinded tapering protocols, 92.9% totally discontinued their medication use by the end of the 20-week tapering phase, whereas 77.3% in the CTRL group discontinued hypnotic use by the end of their open label tapering. At follow-up 72.1% of those who completed blinded tapering remained medication free whereas only 52% of those who underwent open-label tapering remained medication free. Comparisons at follow-up showed those who received the open-label taper continued to use hypnotics on average 2.06 nights/week compared to .051 times per week for the blinded taper group (p = .042). The average weekly diazepam equivalent dose of medication used by the open label tapering group was 11.29 mg whereas the weekly dose for the blinded tapering group was 3.22 (p = .069). Conclusion: CBTI combined with blinded hypnotic tapering is a promising treatment approach for helping hypnotic users overcome their medication dependence. Support (if any): National Institute of Drug Abuse, Grant # R34 DA042329-01